Prospective study to optimize care and improve knowledge on ovarian function and/or fertility preservation in young breast cancer patients: Results of the pilot phase of the PREgnancy and FERtility (PREFER) study. (October 2018) - Lambertini, Matteo; Fontana, Valeria; Massarotti, Claudia; Poggio, Francesca; Dellepiane, Chiara; Iacono, Giuseppina; Abate, Annalisa; Miglietta, Loredana; Ferreccio, Chiara; Pescio, Maria Carolina; Conte, Benedetta; Blondeaux, Eva; et al.
Abstract: Background: Despite the availability of different strategies for ovarian function and/or fertility preservation in young breast cancer patients candidates for chemotherapy, limited data are available on patients' actual need of these options. Patients and methods: The PREFER study is a prospective cohort study including premenopausal women with newly diagnosed early stage breast cancer between the age of 18 and 45 years and candidates for chemotherapy. The study aimed to investigate patients' preferences and their choices of the different available strategies for ovarian function and/or fertility preservation (i.e. acceptance rate) and reasons for refusal. Results: A total of 131 consecutive patients referred from a single breast unit were included. Median age was 38.9 years with 92 patients (70.3%) diagnosed at ≤ 40 years. The majority of patients (122, 93.1%) were concerned about the risk of treatment-induced premature ovarian insufficiency (POI) and/or infertility. A total of 120 (91.6%) patients underwent temporary ovarian suppression with gonadotropin-releasing hormone agonists during chemotherapy for ovarian function preservation. Among patients with ≤40 years, only 11 (12.0%) decided to access cryopreservation strategies for fertility preservation. The main reason for not accessing the fertility unit was completion of family planning before breast cancer diagnosis; for patients who accessed the fertility unit, fear of the procedure was the main reason to refuse the proposed cryopreservation strategies. Conclusion: Despite the majority of young breast cancer patients are concerned about the risk of treatment-induced POI and/or infertility, only a limited number of them required to access the fertility unit to undergo cryopreservation strategies. Highlights: The PREFER study is a prospective cohort study in premenopausal early breast cancer patients. Acceptance rate and reasons for refusal of ovarian function/fertility preservation strategies were explored. 93.1% of patients was concerned about risk of chemotherapy-induced POI and/or infertility. 91.6% of patients underwent GnRHa during chemotherapy for ovarian function preservation. 12.0% of patients decided to access cryopreservation strategies for fertility preservation.